KNOCK DOWN BAMBOO WALL PANEL - Santosa (Jurnal Riset Arsitektur, 2018)
Abstract- Indonesia often experiences natural disasters, therefore a transitional residential building is needed for victims who are able to build quickly and easily in mobilization. Bamboo is a local material that exists in Indonesia and has a high sustainability to be used as building materials. The appropriate principle between the characteristics of bamboo and the needs of transitional buildings where used as wall materials. The knock down bamboo wall panel is the answer of the need for fast and easy work in mobilization.The research method used is qualitative descriptive of two study object and design experiment of prototype 1: 1. Researchers will conduct a study of bamboo walls on two study objects Blooming Bamboo Home dan Soe Ker Tie House, also meetings of any deficiencies and advantages from aspects of form, function and context, and construction. Forms include material used, basic dimensional modules, wall weight, and the ability to re-modify walls. Functions and Contexts include the space privacy, resistance, and behavior of walls against wind, solar heat, lighting, and rain. Construction covers the way of bamboo processing into wall panels, connection systems, and can be done massively by the crowd. Potential bamboo wall variants to be explored will be evaluated and developed for the better and new alternative of other wall panels also considered.The most efficient bamboo knock down panels are bamboo slats and woven bamboo booths as massive walls, woven bamboo and bamboo modified blades I as semi-open walls, modified bamboo blades II and polikarbonate as open walls. The most appropriate connection system used in knock down bamboo wall panels is the gypsum screw connection for bamboo wall panel frame joints, bolt nuts and iron plates for knock down bamboo wall panel connections with structures and connections between wall panels. Keywords: Knock down, Bamboo, Sustainable, Wall panel